AKSESIBILITAS PEMBAYARAN BITCOIN DALAM PERSPEKTIF FIQH EKONOMI - Erizal Candra Efendi; Wildan Hadi, Robi Harjoni Putra, Al Aziz, Hulwati, Duhriah (CV. Adiba Aisha Amira, 2025)
This study examines the potential of Bitcoin as a payment tool that aligns with Islamic principles in the context of economic fiqh. Bitcoin, as a form of cryptocurrency, oflers innovation in the global payment system, particularly for individuals and businesses in developing countries who are marginalized from traditional financial services. With its decentralized nature, Bitcoin can enhance payment accessibility and support financial inclusion. However, challenges such as price volatility, lack of clear regulations, and low financial literacy remain significant barriers to its adoption. This research uses a literature review method to explore how Bitcoin can function as a legitimate alternative in financial transactions, as well as to identify the existing challenges and opportunities. The findings show that while Bitcoin has great potential, comprehensive regulatory development and improved financial literacy are needed to maximize its eflective use. This study contributes to the development of economic fiqh and the digital financial sector, and paves the way for policies that support the growth of Bitcoin as a beneficial payment tool for society, especially in areas with limited access to formal banking systems.